ANALISIS HUBUNGAN INTERPERSONAL PELAKU HIJRAH DENGAN TEMAN NON-HIJRAH : Studi Fenomenologi pada Anggota Komunitas YukNgaji Jakarta - Alya Tazkiya (2021)
Hijrah is now a big phenomenon that occurs in the Indonesian Muslim community. The massive phenomenon of hijrah that occurred in Indonesia is still reaping many opinions, both pros and cons. The effect of the massive migration phenomenon has an influence, one of which is on the interpersonal relationships of the hijrah actor with their friends who are not. This study focuses on analyzing the interpersonal relationship between the two people who want to find out whether there is a change in their interpersonal relationship when the hijrah actor experiences a change in behavior. The approach used in this research is qualitative with phenomenological research methods. The phenomenological method is used because the results of the analysis will be based on the experience of the research subject. Social penetration theory is used as an explanation of the process of interpersonal relationships that are carried out by the two. Data collection was carried out using in-depth interviews with two hijrah actors who were members of the YukNgaji Jakarta community, and two close friends of each hijrah actor. The results showed that there was no significant change in the relationship between hijrah actors and non-hijrah friends so that the relationship was still well established. The relationship that exists is at the engagement stage and does not reach the stage of conflict and disconnection. It can be concluded that the changes that occur in the relationship have nothing to do with the hijrah carried out by the hijrah actors, but are created from the busyness factor and the lack of communication between friends. The researcher also provides suggestions regarding their lack of self-disclosure, that self-disclosure is still important because it can make the relationship between the hijrah actors and non-hijrah friends closer even though there are differences in views and their respective activities.